2005
DOI: 10.2337/diacare.28.3.612
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Glucose Abnormalities and Heart Failure in the Population-Based Reykjavík Study

Abstract: OBJECTIVE -Diabetes is an independent risk factor for heart failure, whereas the relation between heart failure and abnormal glucose regulation (AGR) needs further evaluation. We studied this combination in the Reykjavík Study. RESEARCH DESIGN AND METHODS -The ReykjavíkStudy, a population-based cohort study during 1967-1997, recruited 19,381 participants aged 33-84 years who were followed until 2002. Oral glucose tolerance tests and chest X-rays were obtained from all participants. Cases were defined in accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
195
0
12

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(214 citation statements)
references
References 22 publications
(22 reference statements)
7
195
0
12
Order By: Relevance
“…Studies in heart failure populations reveal a prevalence of T2DM from 12-30%, rising with age. 270,271 In the Framingham study, the age-adjusted relative risk of heart failure in patients with T2DM (age 45-74 years) was 2.2 for men and 5.3 for women. 272 The high incidence of heart failure in patients with T2DM was confirmed in the National Health and Nutrition Examination Survey, with an HR of 1.85 (95% CI 1.51-2.28) in T2DM compared with non-DM.…”
Section: Heart Failure In Type 2 Diabetesmentioning
confidence: 99%
“…Studies in heart failure populations reveal a prevalence of T2DM from 12-30%, rising with age. 270,271 In the Framingham study, the age-adjusted relative risk of heart failure in patients with T2DM (age 45-74 years) was 2.2 for men and 5.3 for women. 272 The high incidence of heart failure in patients with T2DM was confirmed in the National Health and Nutrition Examination Survey, with an HR of 1.85 (95% CI 1.51-2.28) in T2DM compared with non-DM.…”
Section: Heart Failure In Type 2 Diabetesmentioning
confidence: 99%
“…In the Reykjavik study, IGT was shown to be an independent predictor of all-cause mortality to a similar degree to that of DM 36 . In a recent study carried out in Division of Cardiology, Department of Medicine, Kameda Medical Center, Chiba, Japan, it was shown that HF patients with IGT tended to have a higher mortality rate than those without glucose intolerance 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This was possibly from the fact that we only included the hospitalized heart failure subjects and in-hospital outcome was based on mortality and length of hospital stay whereas, in other studies they included both inpatient and outpatient department and long term cohort study was done there. The diagnosis of IGT & IFG in the Reykjavik study, however, was done on 50 gm OGTT, not 75 gm was used in the present study 36 . The European Guidelines on diabetes, prediabetes, and cardiovascular diseases recommend use of 75-g OGTT 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 12% of diabetes mellitus patients have heart failure (54), and over the age of 64 years, the prevalence increases to 22% (56). In several studies, the incidence of heart failure was two-and fourfold higher in patients with diabetes mellitus than in those without (54)(55)(56)(57)(58)(59). The development of heart failure in diabetes mellitus significantly increases mortality (61).…”
Section: Cardiomyopathy With Diabetes Mellitus or Obesitymentioning
confidence: 99%
“…The development of heart failure in diabetes mellitus significantly increases mortality (61). Up to 30% of heart failure patients have diabetes mellitus (55,60,62). In population and clinical trial studies (62-68), heart failure patients with diabetes mellitus have greater mortality rates than those without, and diabetes mellitus is an independent predictor of mortality in heart failure patients.…”
Section: Cardiomyopathy With Diabetes Mellitus or Obesitymentioning
confidence: 99%